Flashboiling-induced targeting changes in gasoline direct injection sprays. (January 2016) - Krämer, Martin; Kull, Eberhard; Wensing, Michael
By definition, flashboiling is referred to as superheated injections. The sudden occurrence of boiling inside the fuel can change the spray structure dramatically. Up to 99% of all injection processes during the New European Driving Cycle and 95% during 'Real Driving Emissions' tests are, with respect to mid-range cars, in a state of thermodynamic non-equilibrium below the specific vapor pressure of gasoline. Considering this fact, the scientific question is not the appearance of flashboiling during the operation of stoichiometric homogeneous charge direct injection gasoline engines but the intensity of occurring spray processes and their influence on nominal spray designs. As a consequence of induced targeting changes, the positive influence of flashboiling on the droplet size distribution and the penetration depth can be counteracted. As main driving factors for targeting changes, jet-to-jet interactions can be identified. By applying appropriate nozzle design features, the potential of flashboiling can be exploited and the targeting changes of the nominal spray designs, considered negatively, are avoided mostly. This work focuses on flashboiling-induced targeting changes, the so-called phenomenon of "spray collapse": its root cause, development and avoidance.